Etmopterus burgessi sp. nov., a new species of lanternshark (Squaliformes: Etmopteridae) from Taiwan - Silva, Jayna A.s.-D.; Ebert, David A. (Zootaxa, 2006)
A new species of lanternshark, Etmopterus burgessi sp. nov., is described from four specimens collected in deepwater off northeastern Taiwan. The new species closely resembles other members of the “Etmopterus lucifer group” in having longitudinal rows of dermal denticles, but can be distinguished from congeners based on the following characters: snout width, gill slit length, caudal peduncle length, second dorsal fin height, the arrangement of flank and caudal markings, tooth morphology, and the presence or absence of dermal denticles. The new species has a broader snout and gill length proportionally longer than other western North Pacific Etmopterus species. Proportionally, E. burgessi has a shorter second dorsal fin height and caudal peduncle length than other Etmopterus species. In addition, both the second dorsal fin and ventral snout surface of E. burgessi have conspicuous dermal denticles. A final distinguishing character of E. burgessi is the flank marking, which resembles E. lucifer.Key-words: Elasmobranchii, Squaliformes, Etmopteridae, Etmopterus, Taiwan